The Role of Nigella Sativa and Phyllanthus Urinaria L Extracts Enhance Inflammation Cytokine and Growth factor in Mesenchymal Stem Cells Conditioned Medium - Ayu, Dian Respati; Irawan, Risky Candra Satria; Prawitasari, Salindri; Shindy, Meirista (International Journal of Cell and Biomedical Science, 2024)
Background: Mesenchymal Stem Cells (MSCs) are cells that have the multipotent ability to undergo self-renewal, differentiate and secrete various bioactive substances, such as chemokines, proteins, microRNAs (miRNAs), growth factors, and cytokines. Conditioned medium of MSC is a medium resulting from cell culture enriched with the secretome of the cultured cells. MSC-CM treated with certain factors can increase the production of growth factors such as VEGF and PDGF, which play a role in angiogenesis and tissue repair. Modification of MSC-CM with bioactive compounds can be a promising strategy to increase the effectiveness of MSCs in medical therapy. Therefore, this study aims to examine whether these herbal extracts can modulate the production of pro-inflammatory cytokines (TNF-α, IFN-γ, IL-1β, IL-6) and growth factors (SDF-1, PDGF, VEGF) in MSC conditioned medium. Methods: This study used a pre-post research design with four treatment groups. Medium culture of MSCs treated with Nigella sativa (doses of 10 µg/mL) and Phyllanthus urinaria L (doses of 25 µg/mL), which were cultured for 24 and 48 hours. Measurement of cytokine and growth factor levels was carried out using the Enzyme-Linked Immunosorbent Assay (ELISA) method for quantitative analysis. Results: The data reveal distinct patterns in the modulation of protein levels, particularly for SDF-1, IL-1β, IL-6, TNF-α, and IFN-γ, which are critical players in inflammation and tissue regeneration. Conclusion: This study showed that the Nigella sativa and Phyllanthus urinaria L extracts in modifying conditioned medium of Mesenchymal Stem Cells is significant release of pro-inflammatory cytokines and growth factors.